A Study on the Adoption of Threat Prevention and Dark Web Monitoring for Information Security Management in India - Guru Prasad, S.; Badrinarayanan, M. K. (Indian Journal of Information Sources and Services, 2025)
World over, organizations are facing the threat of breaches of the Information Technology systems and networks they have deployed. Growing threats to the Information Technology assets, Data, Networks, and Systems put a lot of pressure on organizations and they have to deploy, the right set of technologies and solutions, right set of people and processes to prevent such threats. Protection of the Information technology assets against such breaches and attacks is an important task in every organization. This article aims to study if the Chief Information Security officers have taken adequate steps and measures to protect the organization against threats. This article aims to study if they have deployed threat prevention measures and/or used proactive threat monitoring and management measures.